Beneficiation of corncob and sugarcane bagasse for energy generation and materials development in Nigeria and South Africa: A short overview - Mohlala, Lesego M.; Bodunrin, Michael O.; Awosusi, Ayotunde A.; Daramola, Michael O.; Cele, Nonhlanhla P.; Olubambi, Peter A. (Alexandria engineering journal, 2016)
The challenges of increasing energy demand and advanced materials for infrastructural development in developing countries have necessitated the search for sustainable sources of raw materials. The high amount of agricultural residues generated in Africa owing to vast availability of arable land has been an impetus for solving some of these challenges. Therefore, this review article provides information on beneficiation and challenges of the two largely generated agricultural residues, corncobs and sugarcane bagasse, in Nigeria and South Africa. The estimated quantities of corncob and sugarcane bagasse generated by these countries are reported. The potentials of beneficiating corncob and sugarcane bagasse in energy generation, in materials development and in other purposes such as production of platform chemicals are reviewed and discussed. Various technologies deployable in the beneficiation of these wastes are enumerated, and the benefits and challenges that are associated with beneficiating these wastes are briefly discussed.